(11aS)-7-Bromo-2,3,5,10,11,11a-hexahydro-1H-pyrrolo[2,1-c][1,4]benzodiazepine-3,11-dione - Chao Ma (Acta Crystallographica Section E, 2012)
The title compound, C12H11BrN2O2, was prepared by an intra-cyclization reaction of (S)-1-(5-bromo-2-nitrobenzyl)-5-oxopyrrolidine-2-carboxylic acid methyl ester in the presence of EtOH/Fe. The five-membered pyrrolidinone ring adopts an approximate envelope conformation, while the seven-membered diazepanone ring displays a twisted boat conformation. Intermolecular classical N—H...O hydrogen bonds and weak C—H...O interactions help to stabilize the crystal structure.